1997
DOI: 10.1073/pnas.94.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of a neurophysiological deficit in schizophrenia to a chromosome 15 locus

Abstract: Inheritance of a defect in a neuronal mechanism that regulates response to auditory stimuli was studied in nine families with multiple cases of schizophrenia. The defect, a decrease in the normal inhibition of the P50 auditoryevoked response to the second of paired stimuli, is associated with attentional disturbances in schizophrenia. Decreased P50 inhibition occurs not only in most schizophrenics, but also in many of their nonschizophrenic relatives, in a distribution consistent with inherited vulnerability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
678
1
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,072 publications
(706 citation statements)
references
References 56 publications
19
678
1
8
Order By: Relevance
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the QT elongation on electrocardiogram was used to discover the genes underlying the long QT syndrome, characterized by syncope, ventricle arrhythmias, and sudden death (Keating and Sanguinetti, 2001). In the field of psychiatry, disturbances of P50 auditory evoked response and smooth pursuit eye movements are among the best established endophenotypes present in schizophrenic patients and their unaffected relatives, and linkage studies have already identified the loci involved in chromosome 15q (Freedman et al, 1997) and 6p (Arolt et al, 1996), respectively. In OCD, stratification by 5-HT level could decrease genetic heterogeneity and increase power to identify susceptibility genes in association and linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an association has been demonstrated between the homozygous 113 bp allele on the D15S1360 polymorphism of the CNRNA7 gene and smoking risk in schizophrenia [63]. Taken together, these results suggest that the CHRNA7 gene is likely susceptible to the deficits of P50 sensory gating in schizophrenia [10, 23, 44, 49, 50, 53, 58, 63-67]. Interestingly, a 2 bp deletion in exon 6 of CHRFAM7A, which disrupts the hybrid gene for the CHRNA7 gene, was associated with episodic memory performance in schizophrenia, suggesting that the CHRFAM7A/CHRNA7 locus plays a role in modulating episodic memory function [68].…”
Section: Sensory Gating Deficits In Schizophrenia and α7 Nachrsmentioning
confidence: 97%